Advances in understanding prognosis in myeloma. (8th September 2016) - Smith, Dean; Yong, Kwee
Summary: In the last two decades outcomes in multiple myeloma (myeloma) have greatly improved, due to the introduction of newer, more effective therapies. This improvement is not uniform. Response to treatment and survival remains heterogeneous, with some patients living for 1–2 years whilst others are alive and progression‐free at 10 years. This variation in outcome is due to patient characteristics plus features intrinsic to the myeloma tumour. Alongside the introduction of novel therapies there has been a greater understanding of disease biology and mechanisms of resistance. This has led to an increase in the number of prognostic markers that can be used in myeloma. This is important not only for more accurate counselling of patients in terms of disease outcome, but also in paving the way for risk‐adapted therapy. Both newer and traditional prognostic markers need to be used in the context of planned therapy. Indeed, the prognostic value of certain markers varies according to which therapy the patient receives. As such, these prognostic factors will require constant re‐evaluation as agents with new mechanisms of action are added into the myeloma treatment algorithm. This article summarises current concepts of prognostic markers in myeloma.